THE WEB AS CORPUS AND ONLINE CORPORA FOR LEGAL TRANSLATIONS - GIAMPIERI, Patrizia (Comparative Legilinguistics, 2019)
Legal language is hallmarked by a pedantic and user-unfriendly jargon whose constructs are all but intuitive, not to mention the legal system specificity which makes it unique in every country. Second language (L2) learners or scholars, hence, may find it difficult to understand the language of the law; whereas translators may consider legal lexical phrases and patterns rather intricate to deal with. The literature claims that a practical way to deepen language knowledge can be found in the Web considered as corpus and in online corpora. This paper is aimed at exploring whether commercial search engines, Web concordancers and online specialised corpora can tackle the issues revolving around legal language. In particular, it will investigate whether Google advanced search and the Leeds Web concordancer can be used to meet the requirements of legal language learners, scholars and translators. Furthermore, it will address legal language queries (and results) in an online specialised corpus: the COCA. This paper will provide instances of the soundness of the above-mentioned online resources, especially when used jointly as cross-analysis tools. The shortcomings of one can, in fact, be compensated for by the other(s).